Effectiveness of Garlic (Allium Sativum L.) Skin Extract Cream on the Healing of Rabbit (Orytolagus Cuniculus) Burn Wounds - Ivan Julianus Mesak; Icho Erinda Timur; Tetty Eka Sugiyanto (Universitas STRADA Indonesia, 2023)
Garlic Tuber Skin (Allium sativum L.) contains flavonoids, alkaloids, saponins and tannins. The content of flavonoids, alkaloids, saponins and tannins contained in garlic bulb skin can have an effect on healing skin that has damaged cell tissue due to burns. This study aims to make a cream formulation of garlic bulb peel extract (Allium sativum L.) with various concentrations of 10%, 15% and 20% using adeps lanae cream base, liquid paraffin, stearic acid for the oil phase and TEA, nipagin for the oil phase. water which was then tested for its effectiveness in healing burns in rabbits (Orytolagus cuniculus). The negative control used cream base and the positive control used MEBO cream. The effectiveness test on burns was carried out on the back of a rabbit with a diameter of 1 cm. The wound was smeared twice a day with lidocaine cream and the healing effect was observed for 14 days. The results showed that from the 1st to the 14th day of observation, the burn wound decreased in diameter. It was concluded that cream concentrations of garlic bulb peel extract 10%, 15% and 20% had the fastest healing and wound healing effect on cream with a concentration of 20%.